Search for neutral color-octet weak-triplet scalar particles in proton-proton collisions at root s=8TeV - Khachatryan, V. (2015)
A search for pair production of neutral color-octet weak-triplet scalar particles (Theta(0)) is performed in processes where one Theta(0) decays to a pair of b quark jets and the other to a Z boson plus a jet, with the Z boson decaying to a pair of electrons or muons. The search is performed with data collected by the CMS experiment at the CERN LHC corresponding to an integrated luminosity of 19.7 fb(-1) of proton-proton collisions at root s = 8TeV. The number of observed events is found to be in agreement with the standard model predictions. The 95% confidence level upper limit on the product of the cross section and branching fraction is obtained as a function of the Theta(0) mass. The 95% confidence level lower bounds on the Theta(0) mass are found to be 623 and 426 GeV, for two different octo-triplet theoretical scenarios. These are the first direct experimental bounds on particles predicted by the octo-triplet model.